Cascading Effects of Assumption Violations in an Extension Program Development Model - Susan T. Guynn; Patrick Hiesl; Shari L. Rodriguez; Janet Steele (Journal of Human Sciences and Extension)
The Cooperative Extension Service delivers informal educational programs that can help to improve the lives of citizens and communities. Planning, design, implementation, and evaluation are crucial considerations for Extension programs and serve as the foundation for the Extension Program Development Model. The Extension Program Development Model has underlying assumptions that may not be explicitly stated or apparent to Extension practitioners, but if the assumptions are violated, it can lead to cascading effects that impact the effectiveness of an Extension program. This paper will discuss the assumptions of the Extension Program Development Model and the potential impacts of assumption violations. We present a case study of a hypothetical Extension timber harvesting program that violates one assumption during the planning stage—identifying the target audience—and how the assumption violation cascades throughout the rest of the model. The target audience in the hypothetical Extension timber harvesting program case study uses two forest landowner subpopulations in South Carolina, members of the South Carolina American Tree Farm System, and landowners in South Carolina as described in the National Woodland Owner Survey. Comparisons are made between the two subpopulations that describe the impact of an assumption violation on the Extension Program Development Model.